2001
DOI: 10.1136/adc.84.5.398
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the occurrence of infantile colic in the community

Abstract: Aims-To assess the occurrence of infantile colic in the community and the need for professional help; and to study the influences of potential determinants of infantile colic. Methods-Surveys were identified by a systematic search in Medline (1966-98) and Embase (1988-98). Retrieved publications were checked for references. Studies selected were community based, prospective, and retrospective surveys on the occurrence of infantile colic published in English, German, French, or Dutch. Occurrence rates were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
169
5
33

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(223 citation statements)
references
References 36 publications
16
169
5
33
Order By: Relevance
“…Overall, 14% of the infants in this study had colic, which is in keeping with previously reported colic prevalence estimates of 5%Ϫ19%. 13,16 Similarly, the migraine prevalence of 18% in the mothers is highly in keeping with the 18% 1-year migraine prevalence estimate among women in North America.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Overall, 14% of the infants in this study had colic, which is in keeping with previously reported colic prevalence estimates of 5%Ϫ19%. 13,16 Similarly, the migraine prevalence of 18% in the mothers is highly in keeping with the 18% 1-year migraine prevalence estimate among women in North America.…”
Section: Discussionsupporting
confidence: 55%
“…Infant colic (excessive crying in an otherwise healthy infant) has an incidence of 5%Ϫ19% in prospective studies. 13,16 Normal infant crying increases in the first weeks of life, peaks at 6Ϫ8 weeks of age, and tapers off by age 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…21 Caregivers typically interpret crying as an expression of a need (eg, hunger, wet diaper, or fatigue) and expect the infant to calm down when the need is met. 27 The state's 154 hospitals that provide maternity care account for 250 000 deliveries per year (Fig 2).…”
Section: Discussion What Causes An Adult To Shake An Infant?mentioning
confidence: 99%
“…Among newborns in Western countries, the prevalence of colic is estimated to be between 5% and 28%. 11 The available evidence suggests that IC has multiple independent causes. IC has been attributed variously to infants' difficulty self-regulating, type of feeding, exposure to cow's milk proteins (especially ␣-lactalbumin) in formula or breast milk, exposure to tobacco smoke, and maternal depression or anxiety.…”
Section: Icmentioning
confidence: 99%